2002
DOI: 10.1046/j.1468-1331.2002.00422.x
|View full text |Cite
|
Sign up to set email alerts
|

The recognition, diagnosis and management of cerebral vasculitis: a European survey

Abstract: We have completed a survey of European neurological practice concerning cerebral vasculitis. Twenty-nine respondents from 15 countries provided information concerning the diagnosis and management. The results confirmed the anticipated low frequency of the disease, but also illustrated the power of any putative collaborative effort. Interestingly, there was a wide variation in clinical practice, in particular concerning the perceived importance of cerebral angiography as a diagnostic test and the very common us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
28
0

Year Published

2005
2005
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(31 citation statements)
references
References 17 publications
0
28
0
Order By: Relevance
“…3,7,11,[14][15][16][17]19) Our patient did not receive steroid or immunosuppressive therapies, yet he did not present with any new clinical symptoms or new lesions on MR imaging in the 6 months after surgery. We did not administer steroid therapy even after the small intracerebral hemorrhage occurred, because the diagnosis of PACNS had not been established at that time.…”
Section: Discussionmentioning
confidence: 78%
See 1 more Smart Citation
“…3,7,11,[14][15][16][17]19) Our patient did not receive steroid or immunosuppressive therapies, yet he did not present with any new clinical symptoms or new lesions on MR imaging in the 6 months after surgery. We did not administer steroid therapy even after the small intracerebral hemorrhage occurred, because the diagnosis of PACNS had not been established at that time.…”
Section: Discussionmentioning
confidence: 78%
“…15,16) The etiology and pathogenesis of PACNS remain unclear. PACNS is characterized by inflammation of the intracranial small and medium arteries without systemic disease.…”
Section: Introductionmentioning
confidence: 99%
“…However, in the presence of a "constellation" of clinical and neuroradiological signs fitting for vasculitis, we consider that positive angiographic findings strongly support diagnosis [20,24,30,31]. In these selected cases our diagnostic iter does not proceed to a biopsy.…”
Section: Discussionmentioning
confidence: 89%
“…Although no prospective placebo-controlled trial of immunosuppressive treatment in CNS vasculitis is currently available, large retrospective series of patients with Wegener's granulomatosis and microscopic polyangiitis provide clear support for their use. 20 A Japanese case study reported a 58-year-old woman presenting with sudden headache who had a frontal lobe subcortical hemorrhage that was evaluated only by serial MR angiography. The findings were felt to be consistent with isolated angiitis of the CNS, and corticosteroid treatment was initiated, with resolution of symptoms and favorable outcome on a 7-month follow-up.…”
Section: Discussionmentioning
confidence: 99%